Uso tópico de tetraciclina, dexametasona e aroeira, isolados ou em combinação, para o tratamento de feridas causadas pela peçonha de Bothrops jararacussu em murinos - Silva, Paula Letícia Braga e (2024)
Accidents involving venomous snakes can be considered a concern for public health, especially in tropical and subtropical regions such as: Africa, Asia, Oceania and Latin America, where they occur more frequently, causing considerable morbidity and mortality. The severity of the poisoning depends mainly on the species, size of the snake and access to healthcare, such as adequate serotherapy. The proteases present in bothropic venoms are divided into serine proteases and metalloproteases and are directly related to the appearance of local inflammatory edema, they have a coagulant action, acting through actions such as thrombin like, activating prothrombin. Conventional serotherapy is rarely effective in neutralizing or even treating local tissue damage. In B. jararacussu poisoning, treatment with antibotropic serum is generally used in large doses, but great effectiveness is not seen. The effectiveness of serum therapy, when administered as quickly as possible, has good results for systemic effects, but has limitations for neutralizing local tissue damage. This work aimed to investigate the blocking of the main local effects induced by B. jararacussu venom, through the combined use of tetracycline, dexamethasone and aroeira. For this, an in vivo model was used to evaluate ointments with the aforementioned substances in local poisoning. Two protocols were adopted: 2 hours and 7 days. In addition to the molecular docking evaluation of the aforementioned substances. The results of the aforementioned work demonstrated that the substance with the greatest potential to block the effects of local poisoning was tetracycline. The proteolytic activity was reduced by tetracycline, as well as the anti hemorrhagic activity was more significant when compared to the other substances under analysis. Regarding hemorrhagic halos, the three substances were able to reduce hemorrhagic halos induced by the venom. When analyzing the potential of the substances to induce the production of IL 10, only the tetracycline ointment and the ointment that contained the three substances together were able to induce an increase in this interleukin, on the other hand, the three substances did not reduce the levels of inflammatory cytokines. MPO activity was also evaluated and only tetracycline and the ointment with all substances reduced this enzyme and MDA activity did not show significant results. In view of the above, it is necessary to further investigate the analysis of isolated tetracycline in the face of local poisoning induced by B. jararacuçu.